PERBANDINGAN KEMAMPUAN BERPIKIR KRITIS MENGGUNAKAN MODEL PJBL, PBL, DAN DISCOVERY LEARNING DENGAN KREATIVITAS SISWA - Maynita Sholihawati; Tedi Rusman; I Komang Winatha; Nurdin Nurdin (FKIP Universitas Lampung, 2019)
The aims of this research were to find out the difference of students' critical thinking ability, the interaction of the use of Project Based Learning, Problem Based Learning, and Discovery Learning with regard to students' creativity. This research was a quasi-experimental design with comparative approach. The data were collected through questioner and tests. Furthermore, the data were analyzed by using T-Test and ANOVA through manual calculation and SPSS. This research was conducted at SMAN 1 Batanghari with six classes as population and three classes as sample, which was selected through Cluster Random Sampling. The result of data analysis showed that Count Table or 13,874 3, 13 which means that there was a difference of students' critical thinking ability, the interaction of the use of Project Based Learning, Problem Based Learning, and Discovery Learning and CountTable or 7,878 2, 51 which means there was an interaction between learning model and students' creativity in students' critical thinking ability on Economy.